2009
DOI: 10.1016/j.vetimm.2008.10.321
|View full text |Cite
|
Sign up to set email alerts
|

The piglet as a model for B cell and immune system development

Abstract: The ability to identify factors responsible for disease in all species depends on the ability to separate those factors which are environmental from those that are intrinsic. This is particularly important for studies on the development of the adaptive immune response of neonates. Studies on laboratory rodents or primates have been ambiguous because neither the effect of environmental nor maternal factors on the newborn can be controlled in mammals that: (i) transmit potential maternal immunoregulatory factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
83
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 151 publications
(225 reference statements)
1
83
0
1
Order By: Relevance
“…The IPP appears to be a specialized secondary lymphoid tissue that appears during late fetal life in the absence of environment influences in contrast to the JPP or conventional PP. Certain features of the IPP in fetal and newborn piglets distinguish it from secondary lymphoid tissues like spleen, such as the dominant expression of IgG3, the most primordial IgG for swine and most 59 in the locus (42,46,82). In mice, IgG3 (also the most 39 Cg gene) is important in marginal zone B cells and seems targeted to bacterial polysaccharides in a T-independent fashion (83,84).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IPP appears to be a specialized secondary lymphoid tissue that appears during late fetal life in the absence of environment influences in contrast to the JPP or conventional PP. Certain features of the IPP in fetal and newborn piglets distinguish it from secondary lymphoid tissues like spleen, such as the dominant expression of IgG3, the most primordial IgG for swine and most 59 in the locus (42,46,82). In mice, IgG3 (also the most 39 Cg gene) is important in marginal zone B cells and seems targeted to bacterial polysaccharides in a T-independent fashion (83,84).…”
Section: Discussionmentioning
confidence: 99%
“…The fetal B and T cell repertoires of both species develop without maternal influence and regulatory factors such as maternal IgG that are known to influence fetal immunological development in mice and rabbits (37)(38)(39)(40)(41). However, swine have multiple offspring (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), weigh ,2 kg at birth, and can be conveniently reared in GF isolators after their recovery by cesarean surgery where all environmental and maternal factors are thereafter controlled by the experimenter (41,42). Furthermore, the V H repertoire of swine is well characterized, partially mapped, and has been followed during development using methods that quantify repertoire development and frequency of SHM (43)(44)(45)(46)(47).…”
mentioning
confidence: 99%
“…Using a similar model, Hrncir et al (27) found that bacterial LPS, which is present as a contaminant in mouse food, is needed to develop a healthy phenotype. Unfortunately, available model species are scarce, and most findings under GF conditions are derived largely from a few mammalian species, mainly rodents (28) and swine (29). Only recently, another species, the zebrafish, has emerged as a key and powerful model organism to widen basic and biomedical animal research (30)(31)(32)(33)(34)(35).…”
mentioning
confidence: 99%
“…However, no significantly different immunization schedules have been provided for these patients so far (11,12). Responses to immunizations are complex, requiring the integration of several components of the immune system, including B-and T-lymphocytes, which are under development during the 1st year of life (13)(14)(15). HIV-1 may quantitatively and qualitatively affect these cells in a time-dependent manner.…”
mentioning
confidence: 99%